Megengan Sebagai Sarana Persiapan Menuju Bulan Ramadhan - Aslam Chitami Priawan Siregar; Ni'matut Tamimah (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2023)
Megengan is a means of preparing to face the month of Ramadan both physically and mentally. In this community service, three main methods are carried out to improve the preparation of the community in Kramat Jegu Village, Taman District, Sidoarjo Regency for the month of Ramadhan, both physically and mentally. With this megengan event, there are 2 pieces of advice about the importance of the month of Ramadan and 6 moral values ​​in honoring the month of Ramadhan that people in the area get, so that they can make themselves more connected with the Creator, namely Allah SWT.